Terbutaline-induced neonatal ventricular tachycardia: A case report and review of literature - Phillip Edwin Nehls; Ramachandra Bhat; Lynn A Batten (Wolters Kluwer Medknow Publications, 2020)
Neonatal ventricular tachycardia (VT) is an extremely rare condition. We present a 35-week-old gestation neonate who developed tachycardia following maternal exposure to terbutaline. Upon transfer to our neonatal intensive care unit, an electrocardiogram (ECG) was obtained which was consistent with VT. The arrhythmia did not respond to vagal maneuvers or adenosine but resolved following cardioversion demonstrated on postcoversion ECG. At outpatient follow-up, the infant had no further episodes of arrhythmia. To the best of our knowledge, this represents the first case describing terbutaline-induced fetal or neonatal VT.